2014
DOI: 10.1590/0104-1169.3591.2465
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of chronic pain and self-perceived health among elderly people: a population-based study

Abstract: OBJECTIVE: to identify the prevalence and intensity of chronic pain among elderly people of the community and to analyze associations with the self-perceived health status. METHOD: cross-sectional study with a populational sample (n=934), conducted through household interviews in the city of Goiânia, Brazil. The intensity of chronic pain (existing for 6 months or more) was measured using a numerical scale (0-10) and the self-perceived health through a verbal scale (very good, good, fair, poor, very poor). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 21 publications
5
44
1
18
Order By: Relevance
“…Results of a study on elderly adults, from 6 nursing homes in Hong Kong, that used a geriatric pain assessment scale, showed a pain intensity of 4.51 on a 10-point scale, which was lower than our results (17). A recent study of elderly people that resided in the community setting in Brazil showed that 52.8% of the elderly population suffered from chronic pain; among them 54.6% reported highest or the worst possible pain intensity (18). In our study, the pain intensity measured by the NRS scale showed similar results, therefore, 106 (88.3%) patients rated a pain intensity of 5 or more (moderate to worst pain).…”
Section: Discussioncontrasting
confidence: 97%
“…Results of a study on elderly adults, from 6 nursing homes in Hong Kong, that used a geriatric pain assessment scale, showed a pain intensity of 4.51 on a 10-point scale, which was lower than our results (17). A recent study of elderly people that resided in the community setting in Brazil showed that 52.8% of the elderly population suffered from chronic pain; among them 54.6% reported highest or the worst possible pain intensity (18). In our study, the pain intensity measured by the NRS scale showed similar results, therefore, 106 (88.3%) patients rated a pain intensity of 5 or more (moderate to worst pain).…”
Section: Discussioncontrasting
confidence: 97%
“…In this study, pain was reported by 20 (28%) patients in the lower limbs, and by 17 (24%) associated with the back (lumbar and spine). Similar results were found in studies [3] [18] in which the location of greatest frequency was in the lower limbs, followed by the lumbar region. Authors speculate that pain in these areas can be associated with the positioning of the patient, who remains in the same position for hours, causing discomfort, in addition to corroborate to vascular complications in the lower limbs [3] [19].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, it indicates that an assessment of pain in only a static position can lead to underestimation of the experience/episodes (33) . Recent studies conducted with the community (34) and with institutionalized elderly (19) have revealed that chronic pain is most often reported in the legs, which can compromise the performance of activities that require travel/mobility. This finding highlights the need for adequate training of staff working in Nursing Home with regard to the implementation of strategies that ensure pain assessment is performed at rest and during movement at the beginning of the institutionalization, in order to prevent damage and suffering by mis/undertreatment (35) of the experiences, especially of elderly who do not have pain assessment records in institutions and for those with dementia, because they are significantly less likely to receive painkillers (5) .…”
Section: Discussionmentioning
confidence: 99%